Tungsten solubility and speciation in hydrothermal solutions revealed by in situ X-ray absorption spectroscopy - M. Borchert; M. Borchert; M. A. Kokh; M. A. Kokh; M. Louvel; M. Louvel; E. F. Bazarkina; E. F. Bazarkina; A. Loges; E. Welter; D. Testemale; R. Al Abed; et al. (European Journal of Mineralogy)
Tungsten (W) concentrations in fluids in equilibrium with crystalline tungsten oxide are used to determine thermodynamic parameters for W solubility and W species in hydrothermal fluids. The solubility data were measured in situ at high pressures and temperatures using X-ray absorption. X-ray spectroscopic data measured in situ – with X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) – were applied to characterize the symmetry and the type of atoms of the first coordination shell of W aqueous complexes present in the fluid at given temperatures and pressures. Experiments were performed at up to 400 °C and at pressures of 40, 50 and 60 MPa. With this dataset, we were able to improve constraints for the already-suggested fluid species WO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="fa6a3d1c655e3a1a9feb31b6a98317a5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00001.svg" width="13pt" height="17pt" src="ejm-37-111-2025-ie00001.png"/></svg:svg>, HWO<msubsup>4-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="b6eae26b160dad06c5030a466620317b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00002.svg" width="9pt" height="16pt" src="ejm-37-111-2025-ie00002.png"/></svg:svg>, H2WO<msubsup>40</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="7pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="f65cbc9bcc2e7c68d9dab1c6f1426119"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00003.svg" width="7pt" height="17pt" src="ejm-37-111-2025-ie00003.png"/></svg:svg>, NaWO<msubsup>4-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="848b33a44e3b4138e639b80482e1fbb7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00004.svg" width="9pt" height="16pt" src="ejm-37-111-2025-ie00004.png"/></svg:svg> and NaHWO<msubsup>40</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="7pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="957fb3d072546ec621eb58df8977ed94"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00005.svg" width="7pt" height="17pt" src="ejm-37-111-2025-ie00005.png"/></svg:svg>. Further, we were able to introduce the H3WO<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a9b2fdba183dceff94210c316afa95ef"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00006.svg" width="8pt" height="15pt" src="ejm-37-111-2025-ie00006.png"/></svg:svg> species that is found to be dominant in acidic fluids. No evidence was found for W species involving Cl− as a ligand. The ionic W species found in the fluid are characterized by a tetrahedral complex at alkaline conditions. In neutral to acidic conditions, W complexes with distorted octahedral symmetry are formed. These complexes may be polymerized at temperatures ≤200 °C and W concentrations >10-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="8cf1e8ae621f2c097aac89a396bbafbf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00007.svg" width="35pt" height="13pt" src="ejm-37-111-2025-ie00007.png"/></svg:svg> mol kg−1 H2O. X-ray spectroscopy as well as thermodynamic modeling suggests that polytungstate species are not relevant at equilibrium concentrations found in the solubility experiments of this study (≤10-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d85bcf19a81ce57d4de382d38959b170"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-111-2025-ie00008.svg" width="35pt" height="14pt" src="ejm-37-111-2025-ie00008.png"/></svg:svg> mol W kg−1 H2O in equilibrium with tungsten oxide) or at concentrations reported for natural systems. Using the thermodynamic properties of the species mentioned above, in situ data on the solubility of scheelite can be successfully described. Thermodynamic modeling shows that scheelite solubility and wolframite solubility strongly increase with increasing salinity, especially up to 1 m NaCl (m denotes molality), and vary with pH, which is consistent with earlier reports. Overall, this study provides improved thermodynamic properties for a set of W fluid species that cover a wide range of fluid compositions, which is necessary for understanding the complex processes of W enrichment and mineralization in hydrothermal systems.